Evaluation of Dietary Intervention Effectiveness of Pediatric Outpatients with Failure to Thrive (FTT) and Underweight - Rustom, Marwa; Daradkeh, Ghazi; Al-Muhannadi, Asmaa (British Journal of Healthcare and Medical Research, 2023)
Purpose: The objectives of this study are to determine the change in growth and body weight and to evaluate the effectiveness of nutrition intervention on growth velocity between intensive dietetic intervention and standard dietetic intervention over a 12-month period in children less than 14 years of age, medically diagnosed with Failure to Thrive (FTT) and /or underweight seen by a pediatric dietitian in outpatient dietetics clinic. Methods: This is a retrospective service evaluation of pediatric dietetic outpatient services between January 2021 and December 2021 at AL-Khor Hospital (AKH) in Qatar. Findings: There was an improvement in mean weight z-scores over the 12-month period, with significantly larger improvements in mean weight z-score for the intensive intervention compared to standard care. Multidisciplinary team intervention including pediatric dietitian was associated with significant changes in weight gain and velocity. Conclusion: Dietetic intervention is crucial and beneficial. Multidisciplinary team intervention and control of underlying medical illnesses may also provide additional improvement in growth.